Prevalence and source analysis of COVID-19 misinformation in 138 countries. (March 2022) - Al-Zaman, Md. Sayeed
This study analysed 9657 pieces of misinformation that originated in 138 countries and were fact-checked by 94 organizations to understand the prevalence and sources of misinformation in different countries. The results show that India (15.94%), the USA (9.74%), Brazil (8.57%) and Spain (8.03%) are the four most misinformation-affected countries. Based on the results, it is presumed that the prevalence of COVID-19 misinformation can have a positive association with the COVID-19 situation. Social media (84.94%) produces the largest amount of misinformation, and the Internet (90.5%) as a whole is responsible for most of the COVID-19 misinformation. Moreover, Facebook alone produces 66.87% of the misinformation among all social media platforms. Of all the countries, India (18.07%) produced the largest amount of social media misinformation, perhaps thanks to the country's higher Internet penetration rate, increasing social media consumption and users' lack of Internet literacy.